On the evolution of relative permeability of two-phase flow in rock fractures: the effect of aperture distribution. Issue 4 (October 2021) - Wang, Chen; Jiang, Yujing; Gao, Renzhe; Wang, Xiaoshan
Abstract: Two-phase flow in natural fractures is of great importance in many engineering applications, such as geothermal energy utilization and natural gas recovery. Multiple models of relative permeability were proposed, such as the X model, the viscous coupling model, the Corey model and the v-type model. The diversity of models indicates that the relative permeability is influenced by multiple factors, and the applicability of each model is limited to some specific conditions. In conventional models, relative permeability is expressed as the function of the saturation of a certain phase. However, relative permeability is also influenced by the aperture distribution of the fracture. In this study, visualized two-phase (water-nitrogen) flow experiments were conducted in one pair of fracture replicas, which includes a smooth replica and a plaster replica so that the flow structures can be recorded. These two replicas form a rough fracture, in which the two-phase flow experiment was conducted. In addition, the aperture data of the fracture was imported into the numerical model for simulation. The flow structures in the experiment are reproduced by the simulation, and the numerically obtained relative permeability also has similar features to that of experimentally obtain relative permeability. Then the two-phase flow simulation was conducted in two fractures, whose apertures are in normal distribution. The results show that the relative permeability in both fractures follow the Corey model approximately, but influenced by the aperture distribution obviously, especially the relative permeability of the wetting phase.